Agency in the making: Experiences of international graduates of a TESOL program. (December 2018) - Ilieva, Roumiana; Ravindran, Aisha
Abstract: This article draws on qualitative research conducted with graduates of several cohorts of a TESOL program for international students, and discusses teacher identity and teacher agency co-construction, and the varied material effects of the program on graduates' possibilities to be agentive in their academic and professional contexts by tracing engagement with native speaker ideology and tensions in reconciling teaching goals and professional contexts. The analysis reveals that the impact of the program on graduates to generate possibilities for agentive action develops through the creation of an iterative reinforcement of agency, scaffolded through program readings, conceptual knowledge, and activities within the ecology of a flexible academic space where authoritative discourses in the academic context become internally persuasive professionally (Bakhtin, 1981). A "third space" (Bhabha, 1990) of hybridity reconfigures professional subjectivities allowing the emergence of other positions. Professional identities are linked within space and time through reflective self-awareness of the possibilities for agentive action and performative demands in professional contexts and entail developing context-driven counter discursive enactments of agency.